EVALUASI DAN OPTIMALISASI INSTALASI PENGOLAHAN LIMBAH TINJA KOTA PEKALONGAN - Wardhana, Irawan Wisnu; Karunia, Wina (Universitas Diponegoro, 2009)
Pekalongan is one of city located in Central Java. This city consist of 271.990 people and has 45,25 Km2Â land area divided into 4 kecamatan. To advance public health and clean sanitation, Pekalongan City was facilitated with septage treatment that known as IPLT, this instalation has the maximum capacity up to 39,40 m3/day, but in the real condition this instalation only treat 36 m3/day of septage waste. The effluen of wastewater still have high concentration of BOD, COD, TSS and total coliform. Based on thatÂ problem, this instalation need to be evaluated so we can find the problem exist and take the right solution for optimalizing IPLT. Optimalization plan in this instalation consist of two aspect, there are technical and non tehnical. Technical consist of service, capacity of IPLT, quantity of septage, treatment units, and facilities/basic facilities. And then, non technical consist of workers, operational system, exploiting by other institution, and financial (public contribution). The solution that can be implemented to optimalize the operation of this instalation are redesign the instalation to advance the treatment procces of wastewater, expand serve area to get proper quantity of septage, create institution that concern in septage treatment, calculate the retribution fee which give good financial support for operation and maintanance ofÂ IPLT, create strict regulation about septage disposal and also has their own regulation for under level quality to control the outlet concentration.